Analisis Umur Pakai Transformator Distribusi 800 Dan 1600 kVA Di PDAM Ngagel Surabaya - Oktavianus Rikardus Waro; Aris Heriandriawan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Distribution transformers have a very important role in the electric power system. The lifespan of transformers in electric power systems will decrease over time. The reduced service life of distribution transformers is caused by several factors, including loading, ambient temperature, transformer winding temperature and transformer oil temperature. The author uses quantitative and qualitative research types. This research was conducted to determine the remaining useful life of distribution transformers. The data used in this research are transformer template data and peak load data during the day and night. The results of data processing obtained state that the first transformer's estimated remaining life with a load > 80% is 18 years starting from 2023, the second transformer's estimated remaining life with a load > 80% is 16 years starting from 2023, for the third and fourth transformers it is not calculated because it has been used since 1982 or is around 41 years old. For the winding temperature on the first transformer LBP 84 ℃ and BP 89 ℃, on the second transformer the winding temperature LBP 81 ℃ and BP 96 ℃. Both transformers are still considered good because the hot spot temperature is below the maximum limit set by the IEEE in 1955, namely a temperature of 98 ℃.